Усилить эффективность роли уголовного закона (Journal of actual problems of jurisprudence, 2019)
This article examines presented a draft of the Criminal Code should be revised in the light of the comments, recommendationsand suggestions, as well as the full text of the draft Criminal Code published in the media for public discussion.